2018
DOI: 10.17219/acem/79296
|View full text |Cite
|
Sign up to set email alerts
|

Potential plasma biomarkers of bladder cancer identified by proteomic analysis: A pilot study

Abstract: Background. Bladder cancer diagnosis and surveillance includes cystoscopy and cytology. New methods for the detection of bladder cancer are needed, because cystoscopy is invasive and expensive, and because urine cytology is not sensitive enough. Objectives. The aim of the study was to select potential plasma protein markers for bladder cancer which could be useful in developing a specific laboratory test to improve diagnosis and to establish treatment strategies in order to prevent the recurrence of the diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…Three forms of haptoglobin have been identified which may indicate numerous potential splices variants and post-translational modification of haptoglobin. Our finding is consistent with previous ones reporting elevated haptoglobin levels in Turkish and Polish bladder cancer patients 17,31 www.nature.com/scientificreports/ Under normal physiological conditions Haptoglobin stabilize hemoglobin (Hb) through binding and forming a complex with it. Haptoglobin has also significant protective properties against oxidative damage by Hb 32 .…”
Section: Healthy Controls Lg Tumourssupporting
confidence: 93%
See 2 more Smart Citations
“…Three forms of haptoglobin have been identified which may indicate numerous potential splices variants and post-translational modification of haptoglobin. Our finding is consistent with previous ones reporting elevated haptoglobin levels in Turkish and Polish bladder cancer patients 17,31 www.nature.com/scientificreports/ Under normal physiological conditions Haptoglobin stabilize hemoglobin (Hb) through binding and forming a complex with it. Haptoglobin has also significant protective properties against oxidative damage by Hb 32 .…”
Section: Healthy Controls Lg Tumourssupporting
confidence: 93%
“…Two dimensional gel-electrophoresis (2D-E) combined with mass spectrometry (MS) have evolved greatly and are capable of analyzing and identifying multiple differentially expressed proteins with high sensitivity and specificity 13,14 . Recent years have witnessed tremendous expansion in circulating biomarkers analysis by liquid chromatography/MS to develop bladder cancer biomarkers for diagnosis and/ or prognosis [15][16][17] . In this context several single biomarker molecules, with mechanistic relevance to bladder cancer, have been identified including complement C3b, CYFRA 21-1, ApoA4, ApoE and soluble E-cadherin [17][18][19] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lemańska-Perek et al [ 90 ] analyzed BC plasma samples and found three groups of proteins with different expression levels compared with normal samples. The first group were proteins that should not exist in normal plasma, including fibrinogen γ, plasma transferrin, and C3b.…”
Section: Human Specimens-based Proteomics Biomarkersmentioning
confidence: 99%
“…Proteomics markers identified in different human samples are summarized in Table 4 [ 53 55 57 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 ].…”
Section: Human Specimens-based Proteomics Biomarkersmentioning
confidence: 99%